TONGUE FUNCTION, SALIVARY FLOW RATE AND IgA, IgM AND IgG TOTAL SALIVARY LEVELS IN CHRONIC CHAGASIC PATIENTS - Cristina Martins, Gabrielle; Beghini, Marcela; Barbosa, Ana Rita Campos; Nogueira, Ruchele Dias; Rodrigues, Bárbara Rocha; Pereira, Thiago Lima; de Faria, Juliana Barbosa; Rodrigues, Denise Bertulucci Rocha; de Lima Pereira, Sanivia Aparecida (Revista de Patologia Tropical / Journal of Tropical Pathology, 2019)
Although microscopic alterations have been detected in tongues and salivary glands of chagasic patients and the identification of biomarkers in saliva has proved advantageous, there are no studies evaluating tongue function and total salivary IgA, IgG and IgM levels in chronic chagasic patients. The aim of this study was to evaluate tongue function, salivary flow rate, and total salivary IgA, IgG and IgM levels comparing chronic and non-chronic chagasic individuals. 37 patients were selected: chronic cardiac chagasic patients (n=6), chronic chagasic patients with the associated form of the disease (cardiopathy and megaesophagus) (n=11), and nonchagasic individuals (n=20). The tongue function underwent a phonoaudiological evaluation. The salivary f low rate was measured by sialometry. The total salivary IgA, IgG and IgM levels were evaluated by sandwich ELISA assay. Chagasic patients with the associated form of the disease presented higher salivary flow rate and lower salivary protein levels. No significant differences were noted in the lingual function or in the total salivary immunoglobulin levels among the groups. Although patients with chagasic megaesophagus presented higher levels of salivary flow and lower salivary protein, the fact that there were no significant differences in lingual function and total salivary immunoglobulin levels among the groups led to the conclusion that chronic chagas disease does not modify the lingual function or the total IgA, IgG and IgM salivary levels. The present study was the first to evaluate the function of the tongue and salivary total immunoglobulin levels in Chagas disease.